Intra-articular administration of adrenaline plus an irrigation pump system for visibility during the arthroscopic reconstruction of multiple knee ligaments without a tourniquet - Zhongyu, Xia; Zhen, Yu; Bingqing, Guo; Xintian, Kong; Meifeng, Guo; Jianda, Xu (Frontiers in Surgery, 2023)
Objective: Multiple ligament knee injuries (MLKIs) are a rare but severe systemic trauma. Single surgery at the acute setting is preferred, although with an extended operation time. To avoid the complications associated with tourniquet, we herein describe a method for visibility without tourniquet: intra-articular administration of adrenaline plus irrigation pump system. Study Design: Cohort study; Level of evidence, 3. Methods: From Apr. 2020-Feb.2022, 19 patients with MLKIs were reviewed retrospectively. All patients got intra-articular administration of adrenaline plus irrigation pump system for visibility without tourniquet. The following parameters were assessed: visibility, range of motion, knee stability, visual analogue scale (VAS), Lysholm score, Tegner activity level and International Knee Documentation Committee Subjective Knee Form (IKDC). Results: All patients got followed up at least 6 months. At latest follow up, the mean VAS, ROM, Lysholm score and IKDC were 1.79±0.86, 121.21±10.96, 88.16±5.21 and 88.53±5.06, respectively. The average Tegner activity level decreased significantly from pre-injury to post-operation (5.16±0.83 vs. 3.11±0.88, P<0.001). 17 of the 19 (89.47%) patients had good knee function, while only 2 patient (10.53%) had asymptomatic knee with positive Lachman test. 17 patients (89.47%) got good or excellent visualization during arthroscopy. 3 of 19 (15.79%) patients required an increased fluid pressure to achieve a clear operative view. Two patients converted to tourniquet inflation due to persistent intra-articular bleeding after the use of shavers. Conclusions: The intra-articular administration of adrenaline plus irrigation pump system is recommended as an alternative of tourniquet to achieve a good visual field. Further evidence-based work with larger sample is needed.